Influence of Organic Fertilizer and Licorice Waste on the Growth and Development of Cotton - Ismailov Dauletbay Uzaqbaevich; Allamjarova Gulbakhar (International Journal on Integrated Education, 2022)
The soils of the cultivated fields of the Republic of Karakalpakstan are saline, and the productivity is low. In order to obtain a high yield of agricultural crops in such soils, it is necessary to carry out measures to increase soil fertility. In a field experiment, the effectiveness of using mineral fertilizers, organic fertilizers and licorice waste in feeding cotton was studied. In the obtained data, it was determined that for the good growth and development of the cotton, a good result can be achieved when using organic fertilizers and licorice waste in the amount of 40 and 60 t/ha each. Mineral fertilizers are not used.